Motivasi Pemilihan Lintas Minat Biologi pada Siswa Jurusan Ilmu Sosial - Yendrita Yendrita; Elijonnahdi Elijonnahdi; Rian Utary Anggraini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to determine the level of motivation of students majoring in Social Sciences (IS) in SMA N I Suliki District in choosing Biology cross-interests. Method, this research is quantitative with quantitative descriptive approach. Samples were taken by total sampling technique. The subjects in this study were all grade X students majoring in IS N NI High School in Suliki District who chose cross biology interest totaling 126 people, the data analysis technique was a percentage technique. The results of data analysis showed IS majoring students at SMAN 1 Kec. Suliki chose biology interest based on intrinsic motivation of 70.48% (good) and based on extrinsic motivation of 62.75% (good). Conclusion, the motivation of students majoring in Social Sciences (IS) in choosing cross-interests of biology both intrinsically and extrinsically is good. Keywords: social sciences, intrinsic motivation, extrinsic, cross biological Interests